P247 MR enterography in Crohn's disease: Comparison between diffusion-weighted imaging and intravenous contrast material in detection of active disease. (16th January 2018) - Geccherle, A; Variola, A; Massella, A; Demozzi, E; Oliboni, E; Carbognin, G; Romano, L
Abstract: Background: MR is a crucial diagnostic tool for Crohn's disease (CD). The aim of the study was to determine the performance of diffusion-weighted imaging magnetic resonance enterography (DWI-MRE) compared with contrast material-enhanced MR enterography (CE-MRE) for evaluating bowel inflammation activity in CD. Methods: We retrospectively review 55 consecutive adults patients with CD that underwent clinical assessment, MR enterography, and ileocolonoscopy within 4 weeks. Inclusion criteria were: a) DWI-MRE with the following b values (50, 400 and 800 s/mm2) and CE-MRE and b) histologically examination after colonoscopy. The final study population included 39 patients (19 M, 20 F, mean age 42 years). The results were compared with the histo-pathological examination after colonoscopy as the reference standard. The sensitivity (se), specificity (sp), positive predicting value (PPV), negative predicting value (NPV) and accuracy (acc) of DWI and CE-MR enterography in distinguishing active inflammatory lesions from inactive lesions were deter- mined. Results: DWI yielded se, sp, PPV, NPV and acc of 88%, 82%, 91%, 75% and 86%, respectively, in distinguishing active inflammatory lesions from inactive lesions. Conversely, se, sp, PPV, NPV and acc obtained using CE-MR were 88%, 64%, 84%, 70% and 80%, respectively. Conclusions: DWI-MR enterography was superior to CE-MR enterography for the evaluation of inflammation in Crohn disease, and could be considered as a potential biomarker of active inflammation in CD.